(untitled) (Altre Modernità, 2019)
Ever since the regime of Gaddafi collapsed in 2011, Libya has become the main gateway for people attempting to reach Europe by sea and the focal point of smuggling networks. While such humanitarian crisis is well-documented, the International Organization for Migration reported the existence of slave markets in Tripoli where Africans were sold in the open. This trade was largely still undocumented, until the CNN released a video showing migrants being sold by an auctioneer for the equivalent of 400. International news agencies and networks gave extensive coverage to the event, depicting Tripoli as the city of modern-day slave markets. This paper analyses the reporting following the release of the CNN footage, comparing and contrasting the media construal of the phenomenon from a ‘Southern’ and ‘Northern’ perspective metaphorically standing for the two shores of the Mediterranean Sea. It, therefore, takes into account a corpus of news reports published by Al-Jazeera, Al-Araby, Middle East Eye, on the one hand, and BBC, Reuters and EuroNews, on the other, over a time-span ranging from November (when the video was released) to December 2017. Such news networks were chosen since the former are the main English-language, independent sources of news concerning the Arab world, while the latter are the principal English-language media outlets in Europe. Examination of the texts comprised in the corpus is meant to uncover not only the differences and similarities in the linguistic construal of the event, but is also deemed to offer a lens to frame the power-relations embedded in the spatial and symbolic opposition between Libya and the European countries, thus highlighting how different geo-political actors are discursively portrayed.